2009
DOI: 10.1186/1476-9255-6-26
|View full text |Cite
|
Sign up to set email alerts
|

Rho iso-alpha acids from hops inhibit the GSK-3/NF-κB pathway and reduce inflammatory markers associated with bone and cartilage degradation

Abstract: Background: Rho iso-alpha acids (RIAA) from hops have been shown to have anti-inflammatory properties. To understand the mechanisms, we evaluated the effect of RIAA in cell signaling pathways and inflammatory markers using various in vitro models. We also investigated their therapeutic effect in mice with collagen-induced arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…These preliminary IAA pharmacokinetic studies demonstrated that IAA compounds can be detected and suggests that the structurally similar reduced IAA may also be able to be targeted. Furthermore, there have been toxicity [19] and pharmacokinetic studies investigating reduced IAA, particularly RIAA and TIAA, due to their possible medicinal properties such as weight loss, antidiabetic, anti-carcinogenic and anti-inflammatory [7,8,[20][21][22][23]. Of these, two studies detected RIAA and TIAA in New Zealand white rabbits [7], and one measured RIAA in humans [8], confirming those reduced IAA groups examined were indeed bioavailable.…”
Section: Introductionmentioning
confidence: 65%
“…These preliminary IAA pharmacokinetic studies demonstrated that IAA compounds can be detected and suggests that the structurally similar reduced IAA may also be able to be targeted. Furthermore, there have been toxicity [19] and pharmacokinetic studies investigating reduced IAA, particularly RIAA and TIAA, due to their possible medicinal properties such as weight loss, antidiabetic, anti-carcinogenic and anti-inflammatory [7,8,[20][21][22][23]. Of these, two studies detected RIAA and TIAA in New Zealand white rabbits [7], and one measured RIAA in humans [8], confirming those reduced IAA groups examined were indeed bioavailable.…”
Section: Introductionmentioning
confidence: 65%
“…For MMP-13, IL-1 or TNF treatment causes an increase in the human chondrosarcoma cell line SW1353 after 20-24 h [8]. Similarly, NO donor treatment also causes an increase in human and bovine chondrocytes after 24 h [14] and after 16 h [21].…”
Section: Discussionmentioning
confidence: 95%
“…In comparison with formalin or hydrogen peroxide, the existing USFDA-approved chemicals used for fungal control during egg incubation, hops is much safer for humans. Hops has "gen-erally regarded as safe" (GRAS) status (Konda et al 2009) and has few negative consequences on human health. Infrequently, there are reports of typically mild allergic reactions as a result of frequent skin contact or inhalation (Cookson and Lawton 1953;Newmark 1978;Śpiewak et al 2001;Góra et al 2004;Van Cleemput et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Natarajan et al (2008) indicated surprise that the antimicrobial activity of hops was not used more widely in nonbrewing applications. This has started to change, however, and hops has been evaluated for potential use in livestock rearing (Cornelison et al 2006;Siragusa et al 2008;Wang et al 2010), food preservation (Larson et al 1996), human health (Zanoli and Zavatti 2008;Konda et al 2009), and human personal care (Dumas et al 2009). This initial study demonstrates for the first time that hops has possible utility as an antifungal agent for eggs in production aquaculture.…”
Section: Discussionmentioning
confidence: 99%